Wave and tidal generation devices : reliability and availability - Tavner, Peter J., 1946- (IET renewable energy series ;, 2017)
There are many wave and tidal devices under development but as yet very few are actually in revenue earning production. However, the engineering problems are gradually being solved and there is an appetite to invest in these renewable generation technologies for harsher environments. To some extent the wave and tidal generation industry is following in the wake of the wind industry, particularly learning from the growing experience of offshore wind farm deployment. This book combines wind industry lessons with wave and tidal field knowledge to explore the main reliability and availability issues facing this growing industry.